The Gambia : Poverty Reduction Strategy Paper Second Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
A number of initiatives begun in the Poverty Reduction Strategy Paper (PRSP) remain incomplete and need to be further implemented in the new PRSP. Executive Directors recommend institutionalization of the PRSP process as a comprehensive approach to overall public policymaking. Strengthened governance is a fundamental cornerstone of the PRSP process. The Gambia has to sustain ongoing efforts, especially in strengthening public expenditure management, the investment climate, and internal controls at the central bank. It will be critical for the PRSP process to be open, transparent, and participatory.